KİŞİLERARASI DUYGU DÜZENLEME ÖLÇEĞİ’NİN TÜRKÇE’YE UYARLANMASI - (:unkn) unknown (My University, 2019)
Türkçe bu çalışmanın amacı Hofmann, Carpenter ve Curtiss (2016) tarafından geliştirilen Kişilerarası Duygu DüzenlemeÖlçeği’ni Türkçe’ye uyarlamaktır. Araştırmanın çalışma grubunu 380 üniversite öğrencisi oluşturmaktadır. Ölçeğin Türkçeyeçevrilmesi sürecinde çeviri-tekrar çeviri yöntemi kullanılmıştır. Ölçeğin orijinal formunun faktör yapısı doğrulayıcı faktöranalizi ile incelenmiş, modelin kabul edilebilir uyum gösterdiği görülmüştür. Ölçeğin iç tutarlılık güvenirlik katsayılarıincelendiğinde alt boyutlarının .798 ile .871 arasında değişmekte olduğu görülmüştür. Ölçeğin tamamı için iç tutarlılıkgüvenirlik katsayısı .914 olarak hesaplanmıştır. Ölçeğin test tekrar test korelasyon katsayısı ölçeğin tamamı için .797 olarakbulunmuştur. Kişilerarası Duygu Düzenleme Ölçeği ve Duygu Düzenleme Güçlüğü Ölçeği arasındaki olumlu yönde manidarilişki, ölçeğin ölçüt bağıntılı geçerliğinin kabul edilebilir düzeyde olduğunu göstermiştir. Araştırmanın sonuçları KişilerarasıDuygu Düzenleme Ölçeği’nin Türkçe formunun geçerli ve güvenilir bir ölçme aracı olduğunu göstermiştir.

The aim of the study is to adapt the Interpersonal Emotion Regulation Scale developed by Hofmann, Carpenter and Curtiss (2016) to Turkish. The study group of this research is composed of 380 university students. The translation-retranslation method was used during the process of translating the scale into Turkish. The factor structure of the scale was examined by confirmatory factor analysis and the model was found to have acceptable fit. When the internal consistency reliability coefficients of the scale were examined, it was observed that the internal consistency reliability coefficients of the four factors ranged from .798 to .871. The internal consistency reliability coefficients of the total scale was calculated as .914. Test-retest correlation coefficients for the total scale was found .797. The positive significant correlation between the Interpersonal Emotion Regulation Scale and Difficulties of Emotion Regulation Scale showed that criterion-related validity of scale was acceptable. The results of the study showed that the Turkish version of The Interpersonal Emotion Regulation Scale was a valid and reliable scale.
THE ADAPTATION OF INTERPERSONAL EMOTION REGULATION SCALE TO TURKISH
Keywords: Psikoloji